Evaluating the potential effect of PCSK9 inhibitors on the risk of sudden cardiac death and ventricular arrhythmias: A meta-analysis of randomized controlled trials - Zhang, Lei; Li, Yuan-Yuan; Liu, Xue-Hui; Liu, Hong-Jun; Xu, Qiang (PloS one, 2025)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors are a new class of drugs used for the treatment of dyslipidemia. PCSK9 inhibitors have been shown to remarkably reduce cardiovascular events in patients at high risk, but data on their impact on sudden cardiac death (SCD) and ventricular arrhythmias are limited. This study aimed to evaluate whether PCSK9 inhibitor therapy reduces the risk of SCD and ventricular arrhythmias. PubMed and Embase were searched up to September 1, 2024 and combined with data from ClinicalTrials.gov. Randomized controlled trials of PCSK9 inhibitors with ≥ 450 patients and follow-up of ≥ 48 weeks were considered for inclusion. Primary outcomes were the incidence of SCD and ventricular arrhythmias. We used a random-effects model to synthesize the data, calculating risk ratio (RR) and 95% confidence intervals (CI). Heterogeneity between studies was assessed with I² statistics. Risk of bias was assessed using the Cochrane risk of bias tool. A total of 12 articles with 16 trials involving 90,764 patients were included. The follow-up duration ranged from 48 weeks to 3.4 years. PCSK9 inhibitor therapy did not significantly reduce the risk of SCD (RR 0.83, 95% CI 0.54-1.28; P = 0.40; I2 = 0%), ventricular arrhythmias (RR 0.81, 95% CI 0.60-1.09; P = 0.17; I2 = 0%), and cardiac arrest (RR 1.20, 95% CI 0.61-2.33; P = 0.60; I2 = 0%). PCSK9 inhibitor therapy did not significantly reduce the risk of SCD and ventricular arrhythmias.